Readability Analysis of the Book Let's Understand Arabic at MTs DDI Takkalasi, Barru Regency - Muhammad Saenal; Darmawati; Herdah (IAIN Parepare, 2022)
This study discusses the analysis of the readability of the book Let's Understand Arabic at MTs DDI Takkalasi. This study aims to determine the readability level of Arabic textbooks for class VIII students of MTs DDI Takkalasi. This study used a mixed method with a quantitative and qualitative sequential explanatory design. The location for the research was MTs DDI Takkalasi, Barru district. Based on the results of the research that has been carried out, several points of conclusion were found, that the results of the readability test using the Cloze Test on thirty class VIII students of MTS DDI Takkalas, found that the average of the six texts tested was included in the category of moderate readability (Instructional) for participants educate.